1999
DOI: 10.1074/jbc.274.1.270
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Regulatory and Catalytic Domains in the Apoptosis Nuclease DFF40/CAD

Abstract: The DNA fragmentation factor (DFF) is composed of two subunits, the 40-kDa caspase-3-activated nuclease (DFF40/CAD) and its 45-kDa inhibitor (DFF45/ICAD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 13 publications
4
53
0
Order By: Relevance
“…As described by Gu et al (1999), central domain of DFF45 (amino-acid residues 101-180) is required for the interaction with DFF40 and DFF45 can assist in the synthesis of highly active DFF40. In addition, the catalytic domain of DFF40 is located in its COOH-terminal region (aminoacid residues 290-345) (Inohara et al, 1999). As our mutation searches revealed that NB-C201 cells express wild-type DFF40 (data not shown), it is likely that CDDP-mediated nuclear fragmentation might be regulated in a DFF45-but not in a DFF40-dependent manner.…”
mentioning
confidence: 90%
“…As described by Gu et al (1999), central domain of DFF45 (amino-acid residues 101-180) is required for the interaction with DFF40 and DFF45 can assist in the synthesis of highly active DFF40. In addition, the catalytic domain of DFF40 is located in its COOH-terminal region (aminoacid residues 290-345) (Inohara et al, 1999). As our mutation searches revealed that NB-C201 cells express wild-type DFF40 (data not shown), it is likely that CDDP-mediated nuclear fragmentation might be regulated in a DFF45-but not in a DFF40-dependent manner.…”
mentioning
confidence: 90%
“…In the late 1990s, caspase-3 was found to cleave a novel cytoplasmic protein termed ICAD (for inhibitor of caspase-activated DNase), which is homologous to the DNA fragmentation factor-45 (DFF45), originally described in HeLa cells Liu et al, 1998;Sakahira et al, 1998;Inohara et al, 1999;Sakahira et al, 1999). ICAD normally forms a heterodimer with and inhibits the actions of CAD (or DFF40), the first caspase-activated DNase that is responsible for the DNA fragmentation pattern that is a hallmark of apoptosis.…”
Section: Therapeutic Interventions: Delivery Of Anti-apoptotic Genes mentioning
confidence: 99%
“…The endonuclease can still remain inhibited by the ICAD D1 domain, which interacts with the regulatory domain of CAD thus preventing its proper activation. It has been proposed that the residues of the EDG loop of the CAD CIDE-N domain are important for the nuclease activity, possibly by interacting directly with the CAD catalytic domain [23,24]. The fragments described here could displace the interaction between the ICAD D1 domain and CAD, allowing the regulatory domain of CAD available for the interaction with the catalytic domain.…”
Section: Discussionmentioning
confidence: 91%
“…These truncated peptides share a common feature; they correspond to the CIDE-N domain of the CAD protein, a motive implicated in the protein-protein interaction with ICAD [23]. Moreover, it has been reported than the interaction between the CIDE-N domain of CAD and ICAD is increased when a part of the endonuclease domain is also implicated in this interaction [26].…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation